IMPLEMENTATION OF THE INDEPENDENT VILLAGE PROGRAM POLICY IN COMMUNITY ECONOMIC EMPOWERMENT IN SEKADAU HILIR DISTRICT, SEKADAU REGENCY - Kornelia Meilinda Betsyeba; Martoyo; Herlan (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
The title of this study is "Implementation of the Independent Village Program Policy in Empowering the Local Economy at Sekadau Hilir District of Sekadau Regency". The issue addressed in this study stems from the lack of coordination among village authorities, community members, and relevant institutions, which potentially hampered the program's implementation and reduced the effectiveness of its organizational processes. The objective of this study is to describe and analyze the organizational stages, interpretation, and application within the implementation process of the Independent Village Program policy aimed at empowering the local economy in Mungguk Village at Sekadau Hilir District of Sekadau Regency. This research employs a descriptive method with a qualitative approach. The findings indicated that the organizational stage has been implemented by the Mungguk Village Government through the establishment of an operational structure, including the Activity Implementation Team (known as Activity Implementation Team/TPK), community groups, and other program partners. The interpretation stage, referring to the understanding of village officials and part of the community regarding the substance of the Independent Village Program, remains varied. A significant portion of the general public had a lack of comprehensive understanding of the program's benefits and mechanisms. The application stage, or the actual implementation of the program, was ongoing. However, the outcomes were not yet evenly distributed. Some community members have begun to experience increased income through small-scale enterprises, yet many others have not directly benefited from the program. The study suggests strengthening all three stages; organization, interpretation, and application, to ensure more effective program implementation and greater impact on community economic empowerment. The success of this program largely depends on the active involvement of all stakeholders, effective coordination, and a shared, clear understanding of its objectives and execution mechanisms.